2003
DOI: 10.1001/archpsyc.60.5.490
|View full text |Cite
|
Sign up to set email alerts
|

A Sib-Pair Study of the Temperament and Character Inventory Scales in Major Depression

Abstract: Harm avoidance, reward dependence, novelty seeking, and self-directedness have traitlike characteristics that are related to the familiality of depression. Cooperativeness, self-transcendence, and persistence are also familial, but this appears to be unrelated to depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
180
3
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(218 citation statements)
references
References 17 publications
25
180
3
10
Order By: Relevance
“…One study has even indicated that this increase in ' self-directedness ' has also predictive value for changes in depressive symptoms as measured with BDI (Mazza et al 2009). Therefore, character dimensions may modulate the expression of mood states (Farmer et al 2003 ;Cloninger, 2004 ;Cloninger et al 2010) and our results may shed light on why both depressive symptoms and ' selfdirectedness ' improve during serotonin-altering psychopharmacological treatment.…”
Section: Discussionmentioning
confidence: 69%
“…One study has even indicated that this increase in ' self-directedness ' has also predictive value for changes in depressive symptoms as measured with BDI (Mazza et al 2009). Therefore, character dimensions may modulate the expression of mood states (Farmer et al 2003 ;Cloninger, 2004 ;Cloninger et al 2010) and our results may shed light on why both depressive symptoms and ' selfdirectedness ' improve during serotonin-altering psychopharmacological treatment.…”
Section: Discussionmentioning
confidence: 69%
“…In line with this hypothesis, studies have found that anhedonia can precede the onset of depression (Dryman and Eaton, 1991); shows temporal stability (Oquendo et al, 2004); predicts poor outcome 12 months later (Spijker et al, 2001); and is associated with dysfunctions within the brain reward system (Keedwell et al, 2005;Tremblay et al, 2002). Moreover, reward dependence, a putatively heritable trait associated with maintenance of behavior in response to reward cues, shows trait-like features associated with familiality of depression (Farmer et al, 2003). Collectively, these findings suggest that anhedonia is among the most promising endophenotypes of depression (Hasler et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…For example, anhedonia symptoms often precede the onset of MDD (Dryman and Eaton, 1991) and seem to be relatively stable over time (Oquendo et al, 2004). A sib-pair study showed that the personality construct 'reward dependence' has trait-like characteristics related to the familiality of major depression (Farmer et al, 2003). Given the extensive evidence for associations between impairments of brain reward pathways and addiction (Nestler et al, 2002), familial coaggregation and lifetime comorbidity of substance use disorders and MDD (Kendler et al, 1997;Brook et al, 2002) also suggest persistent familial abnormalities of brain reward pathways in MDD.…”
Section: Anhedonia (Impaired Reward Function)mentioning
confidence: 99%